Multicentre trials on specialised exercise training and rehabilitation are useful in patients with pulmonary hypertension - Grünig, Ekkehard; Benjamin, Nicola; Eichstaedt, Christina (The European respiratory journal, 2019)
Multicentre trials on specialised exercise training and rehabilitation in patients with pulmonary hypertension are needed to provide further evidence on its haemodynamic effects and to show implementation in different healthcare systems is possible.
Gesehen am 25.03.2020